Níveis de atividade física associados às funções cognitivas em mulheres idosas: um estudo caso-controle utilizando sensores de movimento - SANTOS, Andrêza Soares dos (2014)
The assessment of the prevalence of cognitive decline in the elderly population and the association of physical activity level with the cognitive functions is very important because low levels of physical activity may contribute to the decline of cognitive functions. Thus, this study aimed to identify the prevalence of cognitive decline among Brazilians elderly and investigate the association between physical activity and the decline of cognitive function in older women. Firstly was performed a systematic review in electronic databases Medline/ Pubmed and Lilacs using the key words in English: "cognitive deficit", "cognitive decline", "cognitive function" and "cognition" combined with "elderly" and "Brazil" and the descriptors in Portuguese "cognitive impairment", "cognitive decline", "cognitive function" and "cognition" combined with the keywords "elderly" and "Brazil", with articles assessing cognitive decline by Mini instrument Mental State Examination (MMSE). Then we performed the original, observational case-control, with elderly residents in the community, using pedometers in assessing the level of physical activity and the MMSE to assess cognitive function. The prevalence of cognitive decline identified among Brazilians elderly were in the range of 4.3% to 46.8%, varying according to the cutoff points used in the MMSE. In the original study included 122 women (61 cases and 61 controls) matched for age and neighborhood. In the data analysis, the procedures of descriptive statistics were used (frequency, mean) and inferential (Chi-square test, multivariate logistic regression and curve Receiver Operating Characteristic - ROC). Logistic regression analysis showed an association between low number of steps/day and the dependence in basic activities of daily living (ADL), instrumental activities of daily living (IADL) and cognitive decline. The analysis of association between low number of steps/day with cognitive functions was found association with the functions guidance and attention and calculation, even when controlled for age, education and functional capacity. The score ≤ 2.018 number of steps/day appeared as a discriminating criterion in predicting cognitive decline. The wide range of cutoff points used in MMSE makes it difficult to compare studies of cognitive decline among Brazilians elderly, and the results of this study corroborate the literature and the association of physical activity and the decline of cognitive function in the elderly.